2022
DOI: 10.1007/s12008-022-00952-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of video essays and podcasts to enhance creativity and critical thinking in engineering

Abstract: The current demands of the labor market demand a new compendium of skills from engineering graduates. To develop skills at a more complex level, this study analyzed the use of second-generation Video Essays and Podcasts to improve soft skills. The characteristics of students belonging to Generation Z as digital natives were considered and digital platforms were adapted for interaction in social networks to enhance critical thinking and creativity (Criticality). Active learning experiences in different engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Experts 'E1' and 'E6' made another suggestion for the Video Content component, pointing out the requirement for supporting materials, like pictures of pupils completing a task, as proof for the subcomponent of problem-solving. Such a suggestion is in line with the claims made in a number of research on video-based teaching and learning (Caratozzolo et al, 2022;Malisius, 2018;Morgan, 2013;Namin et al, 2021) Expert 'E5' suggested that one of the subcomponents should be video quality, but the other experts disagreed, arguing that the assessment does not specifically focus on video quality. They also asserted that using expensive technology to produce a high-quality video would be out of reach for most students.…”
Section: Discussionsupporting
confidence: 56%
“…Experts 'E1' and 'E6' made another suggestion for the Video Content component, pointing out the requirement for supporting materials, like pictures of pupils completing a task, as proof for the subcomponent of problem-solving. Such a suggestion is in line with the claims made in a number of research on video-based teaching and learning (Caratozzolo et al, 2022;Malisius, 2018;Morgan, 2013;Namin et al, 2021) Expert 'E5' suggested that one of the subcomponents should be video quality, but the other experts disagreed, arguing that the assessment does not specifically focus on video quality. They also asserted that using expensive technology to produce a high-quality video would be out of reach for most students.…”
Section: Discussionsupporting
confidence: 56%
“…It is well-documented that active learning is a highly positive teaching alternative for students' learning and skill development in STEM areas [9,10]. The use of strategies that promote this approach is based on peer interaction, collaborative learning, collective and individual reflection, constructive discussion, feedback, and critical thinking [11][12][13]. These strategies serve as frameworks to enhance students learning in traditionally challenging disciplines, such as physics and mathematics [14][15][16][17][18][19].…”
Section: Framework 21 Active Learning and Stem Educationmentioning
confidence: 99%
“…Although it has its drawbacks, it can be an effective tool for teaching, research, and popularizing science. Understanding and researching clip thinking can help us better understand how people perceive and process information and help us create more effective ways to communicate and learn in the future (Caratozzolo et al, 2022).…”
Section: Application Of Clip Thinking In Education and Sciencementioning
confidence: 99%